HAMBATAN DALAM PENERAPAN PENDEKATANSAINTIFIK DI SEKOLAH DASAR DAN UPAYA MENGATASINYA - Madu, Fransiska Jaiman; Gilbertus L. Targan; Mariana Jediut (JIPD (Jurnal Inovasi Pendidikan Dasar), 2022)
The main issue discussed in this study is the obstacles that teachers experience in applying a scientific approach in elementary school. One of the main reasons for teacher barriers in applying scientific approaches is the limitation of teachers' pedagogical competence and the teacher's lack of understanding of the scientific approach. The purpose of this study is to describe the obstacles faced by teachers in applying a scientific approach in elementary school and efforts to overcome the obstacles faced by teachers in applying a scientific approach in elementary school. This type of research is literature study research. Data collection techniques using documentation techniques. The results showed that: 1) Teacher barriers in applying a scientific approach in elementary school are found in the five main characteristics of the scientific approach, namely: first, observing; teachers experience bullying because some students participate in observing the problems given by the teacher while there are still students who chat or tend to be quiet rather than observing the object given by the teacher; second, ask; teachers have difficulty because students are still less active in asking questions; third, collect information; teachers experience concern because the source of information that elementary students believe only comes from teachers; fourth, associating / reasoning, teachers experience concern when the implementation is announced to be less able or unable to think critically about something; fifth, communicate; Teachers experience bullying because students' speaking skills are still low and most students feel embarrassed to talk to their friends in front of the class. 2) Efforts to overcome the obstacles faced by teachers in applying a scientific approach in elementary school, namely; first, observe; the teacher must create a learning atmosphere that can create student curiosity, as well as can encourage students to observe; second, ask; teachers must know the right learning strategies to increase learning motivation, so that students are active to ask questions, express opinions, and master the material; third, collect information; increased learning facilities and facilities, aiming to facilitate teachers and students in the learning process, then teachers must know the characteristics of students in the midst of a large number of students; fourth, associating; the teacher's efforts in overcoming obstacles to the characteristics of socializing, the teacher makes discussions with small groups; fifth, communicate; Teachers accustom students to communicate the results of group and individual work in front of the class so that their abilities are trained and formed. Keywords: barriers to the application of scientific approaches